2005
DOI: 10.1111/j.1365-2222.2005.02250.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent airway hyper‐responsiveness and inflammation in Toxocara canis‐infected BALB/c mice

Abstract: The presence of Toxocara larva in the lungs at 60 days p.i. following a single infection could explain the persistent pulmonary inflammation, airway hyper-reactivity, eosinophilia and increased IgE production observed in T. canis-infected BALB/c mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
(40 reference statements)
4
45
0
Order By: Relevance
“…One study conducted 30 years ago demonstrated hypersensitivity in lung cells in primates infected with Ascaris suum relative to non-infected animals (Pritchard et al 1983). More recent animal studies have shown compromised lung function in mice infected with other nematodes (Buijs et al 1995;Pinelli et al 2005). Furthermore, results from human studies also support a more specific association between Toxocara infection and asthma in low and middle income countries (Feldman and Parker, 1992;Buijs, 1994;Buijs, 1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…One study conducted 30 years ago demonstrated hypersensitivity in lung cells in primates infected with Ascaris suum relative to non-infected animals (Pritchard et al 1983). More recent animal studies have shown compromised lung function in mice infected with other nematodes (Buijs et al 1995;Pinelli et al 2005). Furthermore, results from human studies also support a more specific association between Toxocara infection and asthma in low and middle income countries (Feldman and Parker, 1992;Buijs, 1994;Buijs, 1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006).…”
Section: Discussionsupporting
confidence: 53%
“…Instead, more insidious chronic disease involving the lungs, vasculature, and central nervous system may be more prevalent and, thus, of greater public health significance (Hotez and Wilkins, 2009). Diminished lung function has been associated with Toxocara infection in animal models, as have infections with other nematodes whose development includes migration across pulmonary tissues (Pritchard et al 1983;Buijs, 1995;Pinelli, 2005 (Feldman and Parker, 1992;Buijs, 1994;1997;Oteifa, 1998;Chan, 2001;Sharghi, 2001;Kuk, 2006), but how this might translate to a high income country with significant health disparities is unknown. Finally, a previous study examining the NHANES III sample population identified a strong association between Toxocara infection and diminished lung function that was robust to many other contributing factors to both toxocariasis and lung function including gender, ethnicity, and rural residence (Walsh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Higher larval recovery from the brain of BALB/c occurred on the 15th day in the female and on the 30th day in the male (P = 0.049535). Pinelli et al (2005) showed that, within the same experimental conditions, recovered T. canis larvae increased in the lung on the 7th day and decreased thereafter, with an accumulation in the brain up to the 56th day. Studies on cerebral toxocariasis have shown that the infective dose influences not only the larval burden in the brain but also the behavior of Toxocara-infected mice (Cox and Holland, 1998).…”
Section: Resultsmentioning
confidence: 95%
“…In fact, the animal model has been widely used to study toxocariasis. Recently, it has been demonstrated that infection of BALB/c mice with T. canis results in chronic pulmonary inflammation and a dominant TH2 type of immune response, regardless of inoculum size (Pinelli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, Toxocara larval stages can migrate into the lung, causing tissue alterations that result in coughing, wheezing, asthma-like symptoms, and pulmonary infiltrate. 58 Dabrowska and others (2012) 59 showed eosinophilic perivasculitis and vasculitis in mice lungs infected with T. canis, and Pinelli and others (2005) 60 showed that mice infected with T. canis develop airway hyper-responsiveness, increased levels of IgE and eosinophils in bronchoalveolar lavage, and increased levels of IL-5 after experimental infection, with the presence of T. canis larvae observed even after 60 days post-infection.…”
Section: Discussionmentioning
confidence: 99%